Keadilan dalam Penolakan Poligami Perspektif Aliran Filsafat Hukum Barat: Studi Putusan No.49/Pdt.G/2023/PA.K - Rahmi Herawati; Arsal (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Applications for permission to practice polygamy raise issues regarding the application of legal requirements and the principle of justice. This study analyzes Decision No. 49/Pdt.G/2023/PA.LK, as it represents a rejection of an application for permission to practice polygamy that is relevant to examine from the perspective of Western schools of legal philosophy. This study employs a normative legal methodology. The results show that the denial was based on the failure to meet legal requirements as well as the need to protect the wife’s rights. Based on the schools of natural law, legal positivism and utilitarianism, the decision reflects justice, legal certainty and utility. This study contributes to strengthening philosophical analysis and serves as a reference for judges in adjudicating cases involving polygamy permits to ensure legal protection that is effective, consistent and oriented toward justice. Furthermore, this study underscores the importance of a legal philosophy approach in understanding judicial reasoning, ensuring that the application of law is not merely based on statutory rules but also accounts for the moral and social aspects within society.